2014
DOI: 10.1007/s10461-014-0762-7
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Challenges Facing HIV-Positive Patients Who Smoke Cigarettes: HIV Viremia, Art Adherence, Engagement in HIV care, and Concurrent Substance Use

Abstract: Evidence suggests that smoking may have negative associations with HIV health outcomes. The smoking rate in our sample of people living with HIV (N = 333) was triple that of the general population (57% v. 19%). Regression analyses revealed that smokers (v. non-smokers) reported lower medication adherence (unstandardized beta = 9.01) and were more likely to have a detectable viral load (OR = 2.85, 95%CI [1.53–5.30]). Smokers attended fewer routine medical visits (β = −0.16) and were more likely to report recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 46 publications
(40 reference statements)
8
56
1
Order By: Relevance
“…Consistent with this, one study of infectious disease clinic patients found through mediational analyses that lower levels of self-reported adherence in smokers might be due to smokers having higher levels of depressive symptoms (24). Similarly, O’Cleirigh et al (22) found that smoking was not only related to non-adherence but that smokers were more likely than non-smokers to endorse problematic alcohol, cocaine, heroin, and marijuana use. On the other hand, Shuter and Bernstein (25) found that current cigarette smoking was a predictor of non-adherence to ART among HIV+ men and women, independent of factors such as drug use history, history of psychiatric illness, and current depression ( n = 64).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with this, one study of infectious disease clinic patients found through mediational analyses that lower levels of self-reported adherence in smokers might be due to smokers having higher levels of depressive symptoms (24). Similarly, O’Cleirigh et al (22) found that smoking was not only related to non-adherence but that smokers were more likely than non-smokers to endorse problematic alcohol, cocaine, heroin, and marijuana use. On the other hand, Shuter and Bernstein (25) found that current cigarette smoking was a predictor of non-adherence to ART among HIV+ men and women, independent of factors such as drug use history, history of psychiatric illness, and current depression ( n = 64).…”
Section: Introductionmentioning
confidence: 97%
“…Research indicates that many factors are related to adherence including covariates of race, such as discrimination (12, 13), psychiatric diagnoses (14,15) such as depression, alcohol or other drug use (1618), stress (18,19), social support (20) and coping styles (21). However, there is emerging literature suggesting that tobacco smoking, which is highly prevalent among HIV+ individuals, may also be associated with poor ART adherence (2226). An estimated 47–70% of people living with HIV/AIDS (PLWHA) smoke cigarettes (24,27,28) and smokers have been shown to be less adherent to a variety of medications (29).…”
Section: Introductionmentioning
confidence: 99%
“…37 Our definition of smoking control in the current study did not take into account long-term cessation, and almost half of the women who recently quit smoking reported a smoking relapse 6 months later (data not shown). Given the substantial health benefits associated with quitting smoking, targeted interventions for HIV-infected women, potentially integrated with other behavioral interventions addressing substance use, 38 should be considered to improve cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Because substances use were measured with an index that puts emphasis on his use in the lapse of the last 30 days, these behaviors must be understood as a variable of contextual nature, interacting with other of accumulative nature and continually modifiable, e.g., behavioral competencies and motives. Thus, from a psychological perspective it is necessary to consider in the analysis the factors of the psychological history -e.g., personality, motives and past behavioral competencies -and those of the present context, to predict and understand why HIV+ persons consistently and efficiently practicing or not medication-adherence behaviors [29][30][31].…”
Section: Discussionmentioning
confidence: 99%